2019
DOI: 10.1016/j.jtumed.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effects of fenugreek seed extract on the biochemical and haematological parameters in high-fat diet-fed rats

Abstract: Objective The present study was carried out to assess the effects of fenugreek seed extract on various biochemical and haematological parameters in high-fat diet (HFD)-fed rats. Methods Female Wistar rats were allocated into five groups (n = 6): 1) control rats, 2) HFD-fed control rats 3) rats fed with HFD and fenugreek (FG) seed extract at doses of 200 mg/kg/day, 300 mg/kg/day, and 400 mg/kg/day for 12 weeks. Blood was collected to examine the biochemical and haematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Fiber galactose and mannose being the main ingredients of the gum are also present in PE‐TFG seeds which help in reducing the lipid levels. A recent study published by the authors, rats fed with high‐fat diet for 12 weeks along with hydro‐alcoholic TFG seed extract in a dose‐dependent manner (200, 300, 400 mg kg –1 day –1 ), showed significantly decreased TC, TG levels with 400 mg kg –1 day –1 (Nagamma et al., 2019). A study focused on HMG‐CoA reductase inhibiting the effect of diosgenin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber galactose and mannose being the main ingredients of the gum are also present in PE‐TFG seeds which help in reducing the lipid levels. A recent study published by the authors, rats fed with high‐fat diet for 12 weeks along with hydro‐alcoholic TFG seed extract in a dose‐dependent manner (200, 300, 400 mg kg –1 day –1 ), showed significantly decreased TC, TG levels with 400 mg kg –1 day –1 (Nagamma et al., 2019). A study focused on HMG‐CoA reductase inhibiting the effect of diosgenin.…”
Section: Discussionmentioning
confidence: 99%
“…The results are expressed as U/l. The oxidative stress marker, TBARS, and GSH, biomarkers of antioxidant defense were estimated as per our earlier reported methods (Nagamma et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The blood samples were tested at a time interval of 3 hr intervals, 0 hr, 3 hr and 6 hrs, using the Veterinary blood cell counter (PCE-210VET, ERMA Inc., Tokyo, Japan). The blood samples were tested for total red blood cells (RBC), white blood cells (WBC), platelet, haemoglobin (Hb), haematocrit, mean corpuscular volume (MCV), mean corpuscular haemoglobin concentration (MCHC) and red cell distribution width (RDW) 11 . The temperature of each box was noted after the biological sample analysis was completed.…”
Section: Evaluation Of Haematological Parametersmentioning
confidence: 99%
“…However, it was associated with oxidative stress and lipid peroxidation as apparent by the increased level of ROS and MDA with a decreased level of total antioxidant activity. Nagamma et al (2019) reported that when decreasing the free radical-scavenging activity of the antioxidants, increased oxidative stress is noticed. El-Sayyad et al (2009) and Kart et al (2010) showed that Cis promoted extreme anomalies in liver tissue histology and the ultrastructure.…”
Section: Effect Of Sprouted Fenugreek Seeds On Serum Mda and Tac Levementioning
confidence: 99%
“…It has been well recognized to have many medicinal properties, such as anti-inflammatory, antidiabetic, antihyperlipidaemic, anticancer, antioxidant, as well neuroprotective activities. Also contains active components such as alkaloids, flavonoids (luteolin, kaempferol, quercetin, tricin, gallic acid… etc), steroids, and saponins (Sushma and Devasena, 2010, Tavakoly et al 2018, Nagamma et al, 2019.…”
Section: Introductionmentioning
confidence: 99%